Comparison of the Effectiveness of an Empowerment-Based Educational Program and Emotion-Focused Therapy on Resilience and Emotion Regulation in Women Experiencing Domestic Violence - Vejdani, Najmeh; Ahmadian, Hamzeh; Yarahmadi, Yahya; Karimi, Qumarth (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The aim of the present study was to compare the effectiveness of an empowerment-based educational program and emotion-focused therapy on resilience and emotion regulation in women experiencing domestic violence in Tehran. Methods and Materials: This study employed a quasi-experimental design with a pretest-posttest approach, including an experimental group, a control group, and a follow-up phase. The statistical population consisted of all women who had experienced domestic violence and visited psychological clinics in Tehran during the first half of 2023. Using convenience sampling, participants were voluntarily selected and assigned to two experimental groups (15 participants in each group) and one control group (15 participants). The experimental group receiving the empowerment-based educational program participated in 10 sessions of 90 minutes each, while the group receiving emotion-focused therapy underwent 12 sessions of 90 minutes each. The control group was placed on a waiting list. The measurement tools used in this study included the Connor-Davidson Resilience Scale (Connor & Davidson, 2003) and the Emotion Regulation Questionnaire (Garnefski & Kraaij, 2006). Data obtained from the questionnaires were analyzed using SPSS software (version 23) through descriptive and inferential statistical methods, including multivariate analysis of variance with repeated measures. Findings: The results indicated that the intervention methods (empowerment-based educational program and emotion-focused therapy) had a significant effect on the components of personal competence, tolerance of negative affect, positive acceptance of change, and personal trust compared to the control group (p < .05). Furthermore, the extent of change in the empowerment-based educational program group for the components of personal competence, tolerance of negative affect, and positive acceptance of change was greater than that in the emotion-focused therapy group (p < .05). Additionally, the findings showed that the intervention methods significantly impacted the components of emotion regulation (p < .05). The extent of change in the empowerment-based educational program group for the components of positive refocusing, self-blame, and blaming others was greater than that in the emotion-focused therapy group (p < .05). Conclusion: It appears that the empowerment-based educational program is more effective than emotion-focused therapy in improving resilience and emotion regulation in women experiencing domestic violence.